Limites e possibilidades da gestão sob o enfoque holístico - Lund, Myrian Layr Monteiro Pereira (2002)
The theme management under a holistic point of view arose from an article published in the september-october 2000 issue of HSM Management Magazine. The article dealt with a new paradigm for managing employees which emphasizes the search for their well-being, where many companies are being obliged to review their human resource policies in order to focus on the three dimensions of the individual: body, mind and spirit. According to the report, the research from Pricewaterhouse-Coopers, Universum and others organizations shows that the balance between word and life is not mirely a demand on the part of present employees, but also one of the main priorities of the new work force coming from Universities the world over. The intense struggle to attract high leveI employees will place companies with :-~ more holistic orientation a step above their competitors. For these companies satisfying the real individual needs of their employees represents a new paradigm in their way of managing business. What changed is the perception that the human being is a primordial factor in competition and is no longer simply raw-material. A tendency in the workmarket began to put the hurnan being at the center, the focus of the relationship. Although this concept appears to be far form the brazilian reality, because of the distance between theory and practice. management model that considers the employee as an integral being, examples now exist of companies that are adopting this principIe. The need for balance between physical, mental. emotional and spiritual aspects in order to be happy cause people to overcome their fear of the unknown and advance with determination toward seIf deveIopment. This study analyzes the use of practices management from a holistic point of view in two different companies. The results show that a holistic treatment is not utopic, but rather represent a challenge for organizations managers who, in arder to achieve this practice successfulIy, need more than implement them. They should adopt them as a philosophy of life. incorporating these concepts into their vaIues and world view. The daily practice ofthe holistic management model needs to begin with CEO to make possible a real transformation from a traditional organization culture to a holistic organization culture possible. The consequence brings an improvement to the econornic financiaI resuIts of the company. In the other hand, we observe the lirnitations in the use of this management model on the part of employees as welI as on the part of executives. Regarding the employees, not alI of them are prepared to accept new responsibilities ar prepared for personal development through seI f knowledge. The beliefs acquired during the educational period, at home or in school, as well as their recent professional experiences, may inhibit the discovering of new possibilities, until they feel compeled to face new knowledge in arder to maintain their competitiveness. Since it is a reIative new management model, not scientifically proven, together wih the difficulty in measuring results objectively and the demand of achieving the goals on a short term, the executives make a priority of administration by goals, because they feel more comfortable about the certainty of getting economic and financiaI results in a short termo They forget however its disasters effects on organization environment which are goingo compromising results on de medi um and long term, whether by the generallack of motivation where employees work under pressure. In tum, many 'entrepreneurs' are beginning to work with the help oftherapists, philosophies and psicologists, first to simulate their own self knowledge, so that they can later implant this new way of seeing the world in their respective companies.